Physiological and anti-oxidative properties of wheat (Triticum aestivum) plant subjected to salt stress - Sarangi, Ansul; Das, Manoja; Behera, Kambaska Kumar; Samal, Nibedita (Journal of Neonatal Surgery, 2025)
India's lakes and oceans, adorned with nature's brushstrokes, offer a sanctuary for reflection, inspiration, and spiritual communion. One of the most remarkable Chilika Lake is its importance as a habitat of its surroundings. It has already been declared a Ramsar site under the Convention on "Wetlands of International Importance" due to its ecological significance. We collected water and soil from it and its surroundings, like Brahmagiri and Gadarodaanga, and observed its physicochemical properties like TDS, PH, conductivity and salinity. The details observations are recorded and are represented with graphs. We learned that water and soil impact the plants in this area, which could be due to salt stress. However, we cannot determine the actual salt concentration of the whole area for which we conducted experiments by taking a different concentration of NaCl solution in our laboratory and extracted antioxidant enzymes like Proline, Malondialdehyde(MDA), Soluble protein Peroxidase and Glutathione, observed to be increasing when the concentration of NaCl increases. Still, the concentration of antioxidant enzymes like catalase, Ascorbate peroxidase, and NADH peroxidase decreases in the leaves of newly grown wheat plants..